Kualiti Perkhidmatan Dan Pencapaian Prestasi Akademik Pelajar: Kajian Kes Di Sekolah Menengah Kebangsaan Agama Al-Irshad Dan Sekolah Menengah Dato' Hj. Abd Kadir - Zakaria, Muhamad Isa (1995)
This study was carried out to look at the service quality and the achievement of the academic perfomance. A Case study was carried out in two schools which situated in Seberang Prai Utara. The schools were Sekolah Menengah Kebangsaan Agama Al-Irshad and Sekolah Menengah Dato’ Hj. Abdul Kadir. The SERVQUAL (Parasuraman, Zeithaml and Beny, 1988) instrument had been used in this research to measure the quality of service. There are 5 dimensions in this service quality. The dimensions were as follow; 1. Realibility, 2. Responsiveness 3. Assurance, 4. Emphaty and 5. Tangibles. The academic perfomance was looked through the 1992,1993 and 1994 PMR examination. Questionnaires were divided into three sections. The sections were: A. For student identity, B. For student expectation and C. For student perception. The questionnaires have 22 items to measure the service quality. Scale 1 to 5 was strongly disaggree and 5 strongly agree. The questionnaires were given to the students through their form teacher. 45 minutes was taken by students to answer the questions. The research finding had shown that the services quality of both schools were negative. The Mean scores at Sekolah Menengah Kebangsaan Agama Al-Irshad is as follow; perceptions 3.2, expectations 4.3 and gap between perceptions and expectations -1.1. At Sekolah Menengah Dato’ Hj. Abd Kadir the research findings as follows; students perception 2.9, students expectation 4.3 and gap between perceptions and expectations -1.4. The research has also show that the relationship between services quality and the academic performance were strong. The value of correlations shows 1. This research has met the objectives. This research is important to schools and the department of education to upgrade their quality of service. Quality management also plays an important role to upgrade the quality of educations in our country.